Long-Term Proton Pump Inhibitor Therapy and its Effect on Endocrine Hormones in Selected Patient Population - Ashfaq, Muhammad; Khan, Qasim; Haroon, Muhammad Zeeshan; Abid, Syed Mobasher Ali; Sharif, Muhammad Junaid Hassan; Alkahraman, Yasser MSA (Hormone and Metabolic Research, 2023)
Proton pump inhibitors (PPI) are commonly prescribed medications for a variety of gastrointestinal disorders around the globe. Long-term utilization of proton pump inhibitors is linked with different adverse events. Although, short-term therapy has been demonstrated to have little or no impact on endocrine hormones in men, yet its safety with long-term use has poorly been studied. We aimed to evaluate the impacts of long-term utilization of proton pump inhibitors on male reproductive hormones and its clinical outcomes. A cross-sectional study was performed in two out-patients gastroenterology clinics in Khyber Pakhtunkhwa province. Male patients who were using PPIs regularly for≥3 months were enrolled in this study. Among 65 enrolled participants, patients with sexual complaints have significant variations in mean serum levels of prolactin (p<0.001), sex hormone binding globulins (p=0.043), total testosterone (p<0.001) and progesterone (p=0.001) as compared to patients without sexual complaints. Significantly high values of prolactin mean ranks were observed in patient with sexual complaints (p<0.001). There were statistically significant correlations of serum levels of sex hormone binding globulins (p=0.003), total testosterone (p=0.008) and progesterone (p<0.001) with serum prolactin levels. Similarly, statistically significant variation was observed for decreased libido (p=0.001), erectile dysfunction (p=0.001) and decreased semen mass ((p<0.001) between normal and hyperprolactinemic PPI users. Highly significant differences were observed in serum sex hormone binding globulins (p<0.001), total testosterone (p<0.001) and progesterone (p<0.001) values in normal and hyperprolactinemic groups. In conclusion, long-term utilization of PPI may induce endocrine hormone disruption with subsequent sexual complications.
Keywords: proton pump inhibitors; long-term; endocrine hormones; sexual disorders; prolactin; testosterone